1992
DOI: 10.1557/proc-279-599
|View full text |Cite
|
Sign up to set email alerts
|

Creation of 3D Patterns in Si by Focused Ga-Ion Beam and Anisotropic Wet Chemical Etching

Abstract: We report the realization of free standing 3D structures as tall as ∼ 7μm with nano-scale thickness in Si using the technique of Ga focused ion beam implantation and sputtering followed by wet chemical etching. Some of the previously investigated subjects such as anisotropie etching behavior of crystalline Si and etch stop effect of Ga+implanted Si etched in certain anisotropie chemical etchants have been further explored with the emphasis on exploiting them in realizing free standing structures. The design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Nanowires implanted with computational areal fluences below 2 × 10 15 cm −2 did not withstand the etching process. This is in good agreement with results of Berry et al [66], Chen et al [69], and Steckl et al [70], which reported the initiation of the etch stop at fluences exceeding 1× 10 15 cm −2 , under similar etching and implantation conditions, but for larger implanted areas.…”
Section: )supporting
confidence: 93%
“…Nanowires implanted with computational areal fluences below 2 × 10 15 cm −2 did not withstand the etching process. This is in good agreement with results of Berry et al [66], Chen et al [69], and Steckl et al [70], which reported the initiation of the etch stop at fluences exceeding 1× 10 15 cm −2 , under similar etching and implantation conditions, but for larger implanted areas.…”
Section: )supporting
confidence: 93%
“…NWs with implanted areal fluences (line fluence/wire width) below 2 × 10 15 cm −2 did not withstand the etching process. This is in good agreement with the results of Berry et al [23], Chen et al [24] and Steckl et al [25], who reported the initiation of the etch stop mechanism at fluences exceeding 1 × 10 15 cm −2 , corresponding to a peak Ga + concentration of 4 × 10 20 cm −3 , under similar etching and implantation conditions but for larger implanted areas.…”
Section: Nanowire Width As a Function Of Fluencesupporting
confidence: 93%
“…The masking effect occurs on p + -layers when silicon is doped by a sufficiently high concentration of boron. 1 The same effect has been found for gallium, [2][3][4][5][6][7] which is also a p-type dopant in silicon. For maskless nanopatterning of silicon, gallium is of special interest because it is used in most focused ion beam ͑FIB͒ tools.…”
mentioning
confidence: 55%
“…This critical dose is a function of etch conditions ͑type of etchant, concentration c, etch temperature T e , and etch time t e ͒ and may by quite different for various geometrical implanted and etched patterns. Summarizing earlier investigations, [2][3][4][5][6][7] by applying different concepts of its determination from the etched structures, the critical dose was defined as D c Ϸ 5 ϫ 10 14 − 1 ϫ 10 16 cm −2 . In the case of completely underetched freestanding cantilevers or bridge structures ͑etch depths of some micrometers͒, higher doses of 1-10 ϫ 10 16 cm −2 are necessary, in contrast to non-underetched patterns with heights up to 0.5 m. Throughout the investigated dose range the implanted layer is completely amorphous, considering the Ga amorphization dose of 1 ϫ 10 14 cm −2 .…”
mentioning
confidence: 99%